2013
DOI: 10.1177/1063426613491286
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing and Internalizing Behavior Problems, Peer Affiliations, and Bullying Involvement Across the Transition to Middle School

Abstract: Continuity and change in children's involvement in bullying was examined across the transition to middle school in relation to externalizing and internalizing behavior problems in fifth grade and peer affiliations in fifth and sixth grades. The sample consisted of 533 students (223 boys, 310 girls) with 72% European American, 25% African American, and 3% Other. Although externalizing and internalizing behavior problems in fifth grade were related to bullying involvement in sixth grade, the prediction of stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 38 publications
(59 reference statements)
5
49
0
7
Order By: Relevance
“…TPJ also shows protracted structural development (Shaw et al, 2008). These social-cognitive and neural developments coincide with increased complexity of children's social interactions (Feiring and Lewis, 1991;Farmer et al, 2015) as socio-emotional understanding increases (Carr, 2011) and variability in social competence widens (Monahan and Steinberg, 2011). One possibility is that these changes in real-world social behaviors are supported by behavioral and neural changes in the mentalizing system, making middle childhood an important time to study mentalizing during real-time social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…TPJ also shows protracted structural development (Shaw et al, 2008). These social-cognitive and neural developments coincide with increased complexity of children's social interactions (Feiring and Lewis, 1991;Farmer et al, 2015) as socio-emotional understanding increases (Carr, 2011) and variability in social competence widens (Monahan and Steinberg, 2011). One possibility is that these changes in real-world social behaviors are supported by behavioral and neural changes in the mentalizing system, making middle childhood an important time to study mentalizing during real-time social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as is the case with bullies, some studies have shown that victims tend to associate with others like themselves, and hence have more difficulty in reacting to protect others. Indeed, the continuity of victimization over time depends on whether school students have friendships or not with other victims (Farmer, et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Vários autores (Cross et al, 2018;Farmer et al, 2015;Pepler et al, 2006) referem que que a transição tem um papel importante sobre os comportamentos agressivos entre pares e, em particular sobre o bullying. A prevalência do bullying parece aumentar após a transição escolar para o 2º ciclo (Cross et al, 2018;Nansel, Haynie, & Simons-Morton, 2007), existindo mesmo um estudo que conclui que mais de metade dos alunos de 6º ano estavam envolvidos em bullying (Nansel et al, 2007), como vítimas ou agressores.…”
Section: Bullying Na Transição Escolarunclassified
“…No entanto, na literatura internacional, não existem muitos estudos longitudinais que analisem a evolução do envolvimento em bullying durante a transição para o 2º ciclo. A maioria dos estudos existentes indicam que os comportamentos de bullying aumentam durante este período (Cross et al, 2018;Pepler et al, 2006) e que a maioria dos alunos que são perpetradores de bullying tendem a manter esse comportamento após a transição escolar (Farmer et al, 2015). No entanto, também existem estudos que apresentam resultados contrastantes, num estudo realizado no Canadá sobre uma transição escolar que ocorreu após o 5º ano, Wang et al (2016) concluíram que a vitimização diminuiu, enquanto a perpretação se manteve estável.…”
Section: Bullying Na Transição Escolarunclassified